Canadian Physicians’ Choices for Their Own Colon Cancer Screening - Mamoon Raza; Charles N Bernstein; Alexandra Ilnyckyj (Canadian Journal of Gastroenterology)
INTRODUCTION: Compliance with colorectal cancer (CRC) screening in Canada is low. The aim of the present survey was to determine whether Canadian physicians older than 50 years were pursuing colon cancer screening. Specifically, physicians were asked to identify their modality of choice and identify their barriers to screening.